Matka Polka Destruktorka – dwa oblicza dysfunkcyjnego macierzyństwa (na przykładzie „Szopki” Zośki Papużanki i „Gorzko, gorzko” Joanny Bator) - Głos, Mikołaj (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The aim of the article is to present two different images of dysfunctional motherhood in contemporary fictional Polish prose on the example of the novel “Gorzko, Gorzko” by Joanna Bator and “Szopka” by Zośka Papużanka. The first of them, represented by the protagonist Violetta Serce of “Gorzko, Gorzko”, fits in the current literature trend of creating an anti-mother character, an enemy who usually perceives a child as a “problem” or is unable or does not want / cannot show him or her feelings, because motherhood it is an obstacle for her. The second is represented by the nameless mother of Zośka Papużanka’s “Szopka”, who identifies the so-called “Gastronomic mother”. The analysis shows that Polish prose of the last two decades still lacks the figure of a mother-friend, and the trauma of being born and growing up in the realities of the PRL’s and capitalism has permanently entered the minds of contemporary writers, destroying optimistic hopes for a successful family life and motherhood.
Polish Mother Destructor – Two Faces of Dysfunctional Motherhood (on the Example of “Szopka” by Zośka Papużanka and “Gorzko, Gorzko” by Joanna Bator)
Keywords: mother; motherhood; matriarchy; trauma; dysfunctional family; matka; macierzyństwo; matriarchat; dysfunkcyjna rodzina